2018
DOI: 10.18535/ijsrm/v6i6.ah01
|View full text |Cite
|
Sign up to set email alerts
|

On-farm Characterization of Barley (Hordeum vulgare L.) Landraces in the Highlands of North Gondar, Ethiopia

Abstract: Barley is an important crop for the North Gondar highlands of Amhara Region, Ethiopia. To assess the characterization of barley landraces, 180 farmers from six villages in three districts of north Gondar zone were selected and surveyed. With regard to distribution status, most of the recorded landraces of barley were endangered. The main end uses of barley in the study area were kolo, beso, tela, injera, korefe, kita and kinche. According to farmers, the main criteria for selecting a variety was varietal chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…We identified 30 different barley landraces in Ethiopia’s Gumer district ( Table 1 and S1 Table ). The landraces identified by the farmers have a local name that describes their characteristic values [ 38 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…We identified 30 different barley landraces in Ethiopia’s Gumer district ( Table 1 and S1 Table ). The landraces identified by the farmers have a local name that describes their characteristic values [ 38 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study's result showed that the majority of farmers (91.3%) who cultivate barely were married. A similar study in Welmera and Ejjera districts also showed that the majority (78%) of farmers who used to grow barley were married [ 22 ]. This may imply that most local farmers who cultivate barley are married.…”
Section: Discussionmentioning
confidence: 96%
“…Farmers designate local names based on characteristics of barley such as spikelet length, dehulling, digestibility, row type, seed size, seed color, yield, kernel color, plant height, and place of origin, use-values, and the person who first introduced the barley to the area. According to the results of various studies, Ethiopian farmers utilize the majority of these traits to identify, name, and describe barley varieties in their areas [ 7 , 9 , 21 , 22 , 33 ]. Similar research, which was done on eset [ 34 ] and on beans [ 35 ], reported that farmers attach local names with different characteristics that are used to describe and differentiate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations